Adsorption of Remazol Blue RR from Textile Effluents Using Leaf Powder as an Alternative Adsorbent - Ana Paula Serafini Immich; Antônio Augusto Ulson de Souza; Selene Maria de Arruda Guelli Ulson de Souza (Adsorption Science & Technology)
Adsorption is one of the techniques used for the effective removal of dyes from industrial effluents, but the adsorption efficiency depends on the choice of a suitable adsorbent. The aim of the present study was to investigate the use of Neem leaves as an alternative adsorbent for the removal of dyes present in textile effluents. The dyestuff studied was the reactive dye Remazol Blue RR. In order to obtain the best removal conditions, the influence of the following parameters was investigated: pH value of the aqueous solution, agitation, addition of sodium sulphate, temperature and adsorbent particle size. A good correlation was obtained when the Langmuir model was applied to fit the experimental data obtained for the concentration of solute adsorbed by the solid phase in terms of the equilibrium concentration of the fluid phase. The experimental data showed that 90% removal of Remazol Blue RR was achievable using Neem leaves as the adsorbent.